PKM PELATIHAN MANASIK DALAM MENINGKATKAN PENGETAHUAN DAN KESIAPAN CALON JAMAAH UMRAH DI PT. ARUDAM 99 CABANG PROBOLINGGO - Ridho, Zainur; Chanif, Moch Ibnu; Romadhan, M Rifki (LPPM Universitas Pamulang, 2024)
Manasik training is very influential on the independence of Umrah pilgrims as well as its positive impact, namely Umrah manasik training has a positive effect on the satisfaction of Umrah pilgrims, Umrah manasik training has a positive effect on Umrah pilgrims when they arrive at the holy land, the aim is to form a study of Umrah manasik because of the lack of knowledge about Umrah manasik, it is not uncommon for the surrounding community who will perform Umrah worship to still look unfamiliar with the ritual activities of manasik which will be practiced later when they arrive on the ground. What are the activities carried out during the manasik, namely providing an explanation of the knowledge of the pillars of Umrah, the prohibition of Umrah, the prohibition of dressing when performing Umrah, and the prayers that are recited during Umrah. Regarding the application of the management system in the Umrah manasik of PT Arudam 99 Probolinggo Branch is said to be consistent. This can be seen from the manasik that is carried out every week on a regular basis, such as the knowledge of the pillars, Sunnah, and obligatory in Umrah.